Quality of Life among Retired Women Sports Person: A Study on the Quality of Life of Retired Women Sports Person (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The global population is ageing is often associated with a decline in health there is a need to further develop preventive health measures. Physical activity can positively influence older adults (aged 50 years and older) health. Population throughout the world are ageing, and the amount of people aged over 65 years is shortly expected the outnumber children under five years old (World health organization, global health and ageing 2011). Physical inactivity is a significant contributor to the development of chronic disease in old age. Therefore regular physical activity is important for older adults health and quality of life. Keeping above points in view researcher made an attempt to study the Quality of life among retired women. The objective is to study the quality of life of retired women sports person using older people quality of life questionnaire.A comparison was made between 30 retired women sports person(not involving in any kind of physical activity or sports) and 30 Active women sports person (actively involving in physical activity or any team and individual sports) on older people quality of life. The sample selected randomly from Bengaluru city, and Bengaluru city stadium, Karnataka. The age range of sample is 60 years and above. The obtained results of the study showed that there is no difference in the quality of life of retired women and Active women sports person. It was concluded that there is no difference between retired women sports person and active sports person. The reason can be both of them were sports person.